2019
DOI: 10.1101/579375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The speed of human social interaction perception

Abstract: The ability to detect and understand other people’s social interactions is a fundamental part of the human visual experience that develops early in infancy and is shared with other primates. However, the neural computations underlying this ability remain largely unknown. Is the detection of social interactions a rapid perceptual process, or a slower post-perceptual inference? Here we used magnetoencephalography (MEG) decoding and computational modeling to ask whether social interactions can be detected… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…The current findings provide insight regarding what visual information is selectively attended by CCTV operators to detect harmful intentions. Previous magnetoencephalography (MEG) study showed that the recognition of human social interactions might involve different visual mechanisms than simple feedforward pattern recognition (Isik, Mynick, Pantazis, & Kanwisher, 2020). The authors found that different types of human social interactions can be decoded at around 500 ms after the onset of videos, which is substantially later than visual processing of objects, faces, emotions, gestures, and actions.…”
Section: Discussionmentioning
confidence: 99%
“…The current findings provide insight regarding what visual information is selectively attended by CCTV operators to detect harmful intentions. Previous magnetoencephalography (MEG) study showed that the recognition of human social interactions might involve different visual mechanisms than simple feedforward pattern recognition (Isik, Mynick, Pantazis, & Kanwisher, 2020). The authors found that different types of human social interactions can be decoded at around 500 ms after the onset of videos, which is substantially later than visual processing of objects, faces, emotions, gestures, and actions.…”
Section: Discussionmentioning
confidence: 99%